Abandoning presumptive antimalarial treatment for febrile children aged less than five years - a case of running before we can walk? - English, M; Reyburn, H; Goodman, C; Snow, R (Public Library of Science, 2009)
Background to the Debate Current guidelines recommend that all fever episodes in African children be treated presumptively with antimalarial drugs. But declining malarial transmission in parts of sub-Saharan Africa, declining proportions of fevers due to malaria, and the availability of rapid diagnostic tests mean it may be time for this policy to change. This debate examines whether enough evidence exists to support abandoning presumptive treatment and whether African health systems have the capacity to support a shift toward laboratory-confirmed rather than presumptive diagnosis and treatment of malaria in children under five.